Evaluation of the Performance of Different Damage Indicators in Railway Bridges. (2015) - Alves, Vinicius; Meixedo, Andreia; Ribeiro, Diogo; Calçada, Rui; Cury, Alexandre
Abstract: This article describes a damage identification methodology based on a genetic algorithm and its application to the numerical model of a railway bridge. The identification method is based on an iterative process that in each iteration compares the values of the bridge's dynamic response for a test damage scenario with the response values for a reference damage scenario. The introduction of damage to the test numerical model is based on the modification of a preselected numerical parameter values. The genetic algorithm allows the identification of damage by minimizing the residue of an objective function constructed from the responses of the test and reference model, and based on the so-called damage indicators. In this study are defined and tested damage indicators based on modal parameters (frequencies and vibration modes) in parameters built from the modal parameters (modal curvatures and flexibility curvatures), and in dynamic responses under action of impulsive loads from frequency response functions (FRFs). The proposed methodology for identifying damage was tested based on a two-dimensional numerical finite element model of a railway bridge including the railway track. The results allowed evaluating the efficiency and reliability of the methodology and of the damage indicators which, in most situations, showed potential in the detection, location and quantification of the severity of the damage.